Development of the Russian socio-economic system: challenges and prospects - Vaslavskaia I. I., Mikhalev D. A., Salishev S. N., Seiubergenova D. S., Ismanov T. K., Salishev S. N., Seiubergenova D. S., Ismanov T. K., Meshcheriagina V. A., Minakov A. V., Markelova I. V., Sizova A. S., Babushkin E. R., Fedorova I. A., Sorokoumov N. I., Ryzhkov M. A., Naidenov N. D., Kuznetsov I. V., Kugai A. I. (Development of the Russian socio-economic system: challenges and prospects, 2025)
the chapter examines the transformation of Russia’s investment market in the context of achieving technological sovereignty. It analyzes the reorientation of investment flows from Western partners to Global South countries. Special attention is paid to the role of state policy in stimulating investments through national megaprojects aimed at ensuring technological sovereignty. The research concludes that regional investments not only help adapt to external constraints, but also foster the development of domestic technological capabilities.
Keywords: инновации; экономическая безопасность; технологии; инвестиции; устойчивое развитие; sustainable development; investments; economic security; innovations; technologies; региональная политика; технологический суверенитет; technological sovereignty; regional policy